Nutrition strategies for obesity management - Diyah Eka Andayani; Vitia ajeng Nur Linda; Fadilah; Diana Sunardi (Indonesian Nutrition Association, 2026)
ABSTRACT Background Obesity is a chronic disease that necessitates nutritional strategy for effective weight management. Behavioural modification relating to nutrients intake, food selection and dietary patterns are essential for sustaining long-term outcomes. Many diets intervention have been developed to facilitate weight loss among obesity patients. Objective This literature review aims to provide an in-depth exploration of nutrition-based strategies that can effectively address the obesity epidemic and their applicability in the Indonesian context. Methods This literature review was conducted in Google Scholar, Pubmed, and Sciencedirect between 1987-2024. The research term are “Obesity” “Diet” “Strategies” “Weight loss”. Results Several diet approaches are utilized in weight-control programs, including traditional calorie restriction, intermittent fasting, low-carbohydrate and low-fat diets, plant-based diets, the Mediterranean diet, and personalized/mindful eating. These diets differ in the quantity and type of food consumed, timing of food intake, and other influencing factors. Conclusions The optimal dietary approach for weight loss depends on individual preferences, metabolic factors, and health considerations. Given the potential alignment between the Mediterranean diet and traditional Indonesian foods, it may serve suitable and sustainable long-term option in the Indonesian context.